Identification and characterization of CYP71 subclade cytochrome P450 enzymes involved in the biosynthesis of bitterness compounds in Cichorium intybus - De Bruyn, Charlotte; Ruttink, Tom; Lacchini, Elia; Rombauts, Stephane; Haegeman, Annelies; De Keyser, Ellen; Van Poucke, Christof; Desmet, Sandrien; Jacobs, Thomas B.; Eeckhaut, Tom; Goossens, Alain; Van Laere, Katrijn (Frontiers in Plant Science, 2023)
Industrial chicory (Cichorium intybus var. sativum) and witloof (C. intybus var. foliosum) are crops with an important economic value, mainly cultivated for inulin production and as a leafy vegetable, respectively. Both crops are rich in nutritionally relevant specialized metabolites with beneficial effects for human health. However, their bitter taste, caused by the sesquiterpene lactones (SLs) produced in leaves and taproot, limits wider applications in the food industry. Changing the bitterness would thus create new opportunities with a great economic impact. Known genes encoding enzymes involved in the SL biosynthetic pathway are GERMACRENE A SYNTHASE (GAS), GERMACRENE A OXIDASE (GAO), COSTUNOLIDE SYNTHASE (COS) and KAUNIOLIDE SYNTHASE (KLS). In this study, we integrated genome and transcriptome mining to further unravel SL biosynthesis. We found that C. intybus SL biosynthesis is controlled by the phytohormone methyl jasmonate (MeJA). Gene family annotation and MeJA inducibility enabled the pinpointing of candidate genes related with the SL biosynthetic pathway. We specifically focused on members of subclade CYP71 of the cytochrome P450 family. We verified the biochemical activity of 14 C. intybus CYP71 enzymes transiently produced in Nicotiana benthamiana and identified several functional paralogs for each of the GAO, COS and KLS genes, pointing to redundancy in and robustness of the SL biosynthetic pathway. Gene functionality was further analyzed using CRISPR/Cas9 genome editing in C. intybus. Metabolite profiling of mutant C. intybus lines demonstrated a successful reduction in SL metabolite production. Together, this study increases our insights into the C. intybus SL biosynthetic pathway and paves the way for the engineering of C. intybus bitterness.